Diseño arquitectónico de un centro de desarrollo integral infantil neurodiverso especializado en el trastorno del espectro autista para Guayaquil - Herrera Maldonado, Génesis Betsabe (2024)
The architectural design of a neurodiverse Comprehensive Child Development Center specialized in Autism Spectrum Disorder for the city og Guayaquil is base don the creation of functional spaces that provide confort to userd, specifically responding to the needs of children disgnosted with said diagnosed, throught the application of design strategies and the use of sensory architecture. This Project solves the major problema of the lack of establishments with adequate infrastructure that provide specialized help to children with Autism Spectrum Disorder in Ecuador, which promote inclusion and improve the quality of life of minors. The architectural design responds to a comprehensive Development Center, therefore, it includes all the therapeutic areas necessary to carry out a correct treatment for Autism, complemented with Green spaces, recreation and socialization areas. All the characteristics and needs of childrens have been considered, Fromm its diagnosis to the treatment to cope with it, adapted to the space, resulting in a harmonious and comfortable architectural solution, creating environments of relaxation, social isolation, recreation, learning, sensory, therapeutic with the nature.